2011
DOI: 10.1007/s12098-011-0491-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Respiratory Syncytial Virus Infection among Hospitalized Children Presenting with Acute Lower Respiratory Tract Infections

Abstract: RSV infection is a significant cause of morbidity among children presenting with ALRI in southern India. In resource-limited settings, DFA can be used as an important tool for rapid detection of RSV and can potentially eliminate prolonged hospitalization and unnecessary use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…These findings were concordance with earlier reports from other states in India. The reported percentage positivity of RSV in Pune, Delhi, Haryana, Assam, Kolkata, and Bangalore was 18.6, 17.4, 23.4, 7.9, 10.3, and 21.1% respectively . The reported percentage positivity in other part of the world was 37% in Japan, 22.42% in Iran, 26% in Brazil, and 26.4% in Mexico .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings were concordance with earlier reports from other states in India. The reported percentage positivity of RSV in Pune, Delhi, Haryana, Assam, Kolkata, and Bangalore was 18.6, 17.4, 23.4, 7.9, 10.3, and 21.1% respectively . The reported percentage positivity in other part of the world was 37% in Japan, 22.42% in Iran, 26% in Brazil, and 26.4% in Mexico .…”
Section: Discussionmentioning
confidence: 95%
“…Out of 22 sequences, 17 (77%) were clustered into newly designed NA1 genotype, and 5 (23%) sequences were clustered into novel ON1 genotype within NA1 genotype. ON1 genotype sequences showed 72 nucleotides (24 amino [22][23][24][25][26][27] The reported percentage positivity in other part of the world was 37% in Japan, 22.42% in Iran, 26% in Brazil, and 26.4% in Mexico. [28][29][30][31] The RSV has a definite seasonality; it occurs winter in temperate regions, monsoon season in tropical regions and autumn in semi-tropical areas.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…In a study performed by Boivin et al, [15] 46 % and 51 % RSV were detected by the real-time PCR method in 204 nasopharyngeal samples of children. Out of 77 samples tested for RSV with DFA, 17 (22.1 %) were found RSV-positive with a mean age of 8.24±7.21 mo in children by Gupta et al, [16]. Of the 126 patients, 46.66 % children were positive for RSV while 58.33 % were negative for RSV between the age of 4-24 mo by Hemalatha et al, [17].…”
Section: Discussionmentioning
confidence: 97%
“…Broor et al reported 30% bronchiolitis with causative agent as RSV. 7,8 We used amplification technique Reverse transcriptase RT-PCR. This was supported by Javed Akhtar etal.…”
Section: Incidence Of Rsv Brochiolitismentioning
confidence: 99%